Perkembangan Wayang Alternatif di Bawah Hegemoni Wayang Kulit Purwa - Riyanto, Bedjo; Mataram, Sayid (PANGGUNG, 2018)
ABSTRACTPuppet as a creative product is often interpreted narrowly only in the art of wayang purwa performances which in the evolutionary span of many centuries most show its adaptive ability. Hegemony of puppet art as one of Javaneses most valuable cultural creativity products, on the other hand, has a negative impact on the evolution of Javanese culture itself. The process of wayang refinement, as a classical art of excellence in the exclusive cultural pockets of the palace, at the same time gained the challenge from the outside which made the puppet art a popular cultural product of kitch that was considered merely an insignificant entertainment. The emergence of contemporary puppet works from Indonesian artists signifies the development of movement in the effort to interpret, explore, and develop traditional puppet art entering the wider arts field so that puppet art does not become a frozen art.Keywords: alternative puppet, hegemony, shadow puppet PurwaABSTRAKWayang sebagai suatu produk kreatif sering ditafsirkan secara sempit hanya pada seni pertunjukan wayang Purwa yang dalam rentang evolusi berabad-abad paling menunjukkan kemampuan adaptifnya. Hegemoni seni pewayangan, sebagai salah satu produk kreativitas budaya Jawa paling adiluhung, pada sisi lainnya berdampak negatif pada evolusi kebudayaan Jawa itu sendiri. Proses refinement wayang, sebagai seni adiluhung klasik dalam kantung-kantung budaya ekslusif kraton dalam saat yang sama mendapat, tantangan dari luar yang membuat seni pewayangan menjadi produk budaya populer yang bersifat kitch yang dianggap hanya sekadar hiburan yang tidak bernilai. Kemunculan karya wayang kontemporer dari para seniman Indonesia menandakan adanya gerak perkembangan di dalam usaha menafsirkan, mengeksplorasi, dan mengembangkan seni pewayangan tradisional memasuki medan kesenian yang lebih luas sehingga seni pewayangan tidak menjadi seni yang beku.Kata kunci: wayang alternatif, hegemoni, wayang kulit PurwaÂ Â